2006
DOI: 10.1073/pnas.0601533103
|View full text |Cite
|
Sign up to set email alerts
|

Activation and repolarization of the normal human heart under complete physiological conditions

Abstract: Knowledge of normal human cardiac excitation stems from isolated heart or intraoperative mapping studies under nonphysiological conditions. Here, we use a noninvasive imaging modality (electrocardiographic imaging) to study normal activation and repolarization in intact unanesthetized healthy adults under complete physiological conditions. Epicardial potentials, electrograms, and isochrones were noninvasively reconstructed. The normal electrophysiological sequence during activation and repolarization was image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
168
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(204 citation statements)
references
References 29 publications
(55 reference statements)
31
168
2
3
Order By: Relevance
“…The leading pacemaker site can, however, move spontaneously along the terminal crest of the right atrium, a phenomenon known as the wandering pacemaker. In open heart surgery, patients and in healthy individuals, the leading pacemaker site has been shown to be located anywhere along the terminal crest between the openings of the superior and inferior caval veins (Boineau et al, 1988;Ramanathan et al, 2004;Ramanathan et al, 2006). Such findings are in agreement with studies on smaller mammals.…”
Section: Introductionsupporting
confidence: 82%
“…The leading pacemaker site can, however, move spontaneously along the terminal crest of the right atrium, a phenomenon known as the wandering pacemaker. In open heart surgery, patients and in healthy individuals, the leading pacemaker site has been shown to be located anywhere along the terminal crest between the openings of the superior and inferior caval veins (Boineau et al, 1988;Ramanathan et al, 2004;Ramanathan et al, 2006). Such findings are in agreement with studies on smaller mammals.…”
Section: Introductionsupporting
confidence: 82%
“…Recent investigations in humans have confirmed that the earliest epicardial electrical break-through occurs in the right ventricular free wall and the anterior LV wall, and then travels in an apex-to-base direction (36). The basal posterior wall is the last region to be activated, which occurs during the down-slope of the R-wave (36). The timing and sequence of electrical excitation in the ventricles is influenced by the impulse propagating through the His-Purkinje system and the anistropic nature of myocardium where propagation velocities are faster along rather than across the fibers (35,37).…”
Section: Electrical Sequence Depolarizationmentioning
confidence: 98%
“…Recent investigations in humans have confirmed that the earliest epicardial electrical break-through occurs in the right ventricular free wall and the anterior LV wall, and then travels in an apex-to-base direction (36). The basal posterior wall is the last region to be activated, which occurs during the down-slope of the R-wave (36).…”
Section: Electrical Sequence Depolarizationmentioning
confidence: 99%
“…28,43,58,60 Recently, both the potential-based approach (for computing epicardial potentials, electrograms, and isochrones) and the activation-time approach were applied and evaluated in human subjects. 28,33,47,49,[57][58][59][60]65,67,[77][78][79] Both methods require discretizing the heart and torso surfaces into continuous non-overlapping mesh elements, a procedure called meshing. Meshing is difficult to apply to irregular surfaces 37 and can introduce mesh-related artifacts, especially in the computation of solutions to the ill-posed 76 electrocardiographic problem, if mesh optimization is not carefully done.…”
Section: Introductionmentioning
confidence: 99%